Nutritional status and effect of seaweed chocolate on anemic adolescent girls - A. Thahira Banu; S. Uma Mageswari (Food Science and Human Wellness)
The study was carried out to study the nutritional status, develop a product incorporating seaweed and assess its impact on anemic adolescent girls. Five hundred adolescent girls in the age group of 15–18 years were selected from a women's college at Kilakarai, Tamil Nadu, India as the target group to find the prevalence of anemia. Among the 500 subjects 100 with a hemoglobin level of 7–9 g/dL (moderate anemia) were selected by purposive sampling technique for supplementation. Seaweed incorporated chocolate was formulated, standardized, tested for consumer acceptability and in vitro iron bioavailability and supplemented to the selected subjects. The result of the study indicates that seaweed chocolate developed obtained the highest score for overall acceptability, 56 mg of iron/100 g and 11.80 mg of bioavailable iron. The results were found to be promising as there was a significant increase in hemoglobin, TIBC, MCH, MCV, serum iron and serum ferritin levels in the selected subjects. Seaweeds are a less consumed natural resource but abundantly available in the coastal areas of India as they are rich source of nutrients and can be used as an effective therapeutic and nutrient adjunct.